A Combination of IBA and NAA Resulted in Better Rooting and Shoot Sprouting than Single Auxin on Malay Apple [Syzygium malaccense (L.) Merr. & Perry] Stem Cuttings - Yusnita Yusnita; Jamaludin Jamaludin; Agustiansyah Agustiansyah; Dwi Hapsoro (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
This research aimed to study effects of IBA, NAA and their combination on rooting and shoot sprouting in Malay apple cuttings. Cuttings from superior genotype were collected and treated with (in ppm w/w): 0, 2000 IBA, 4000 IBA, 2000 NAA, 4000 NAA, 1000 IBA+1000 NAA, 2000 IBA+2000 NAA. To record the timing and percentage of rooting, cuttings were treated with (in ppm w/w) 1000 IBA+1000 NAA or without auxin as control. The results revealed that application of auxin was significantly enhanced root formation as shown by the significant increases in rooting percentage and number of roots. NAA at 2000 or 4000 ppm was the most effective auxin to promote root formation (100 %, 17.8–25.5 roots per cuttings), followed by NAA+IBA (100 %, 16.8– 9.8 roots per cuttings) and the least effective was IBA alone (79-100 %, 3.2–7.1 roots per cutting). The best treatment for rooting and shoot sprouting were (in ppm) 1000 IBA+1000 NAA, since it produced higher root length, better root morphology and higher shoot sprouting. It was also found that a combination of IBA+NAA each at 1000 ppm not only enhanced root percentage, but also shortened the time for root formation.